2010
DOI: 10.1038/ijo.2010.225
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the pattern of weight change from pregnancy to 6 months postpartum: a latent growth model approach

Abstract: We found that weight change from pregnancy to postpartum followed a pattern that could be specified using the LGM approach. The women retained more than 6% of weight at 6 months postpartum compared with their pre-pregnancy weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…To our knowledge, this is the first study assessing the relationships between breastfeeding and PWR in a nationally representative sample in Asia. Only 36.6% of women in our study returned to their pre-pregnancy weight after six months postpartum, however, this percentage was higher than has been previously reported-20% in Taiwan [21] and 13-20% in the US [1]. Different study populations and measurement methods could possibly explain the higher percentage of women returning to their pre-pregnancy weight in our study.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…To our knowledge, this is the first study assessing the relationships between breastfeeding and PWR in a nationally representative sample in Asia. Only 36.6% of women in our study returned to their pre-pregnancy weight after six months postpartum, however, this percentage was higher than has been previously reported-20% in Taiwan [21] and 13-20% in the US [1]. Different study populations and measurement methods could possibly explain the higher percentage of women returning to their pre-pregnancy weight in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…To the best of our knowledge, only two Taiwanese studies explored the relationship between breastfeeding and PWR. A cohort study with 120 women did not find an association between breastfeeding and PWR [21], however a more recent study with a larger sample size (N = 461) showed a significant negative association between exclusive breastfeeding and PWR [22].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Similar to other studies [24], we selected this period to strike a balance between allowing enough time for initial pregnancy-related weight loss to occur, while still intervening early enough to prevent long-term postpartum weight retention, which has been independently related to future weight gain and the development of obesity [15]. Women must be currently overweight or obese, with a body mass index (BMI) of 25 kg/m 2 or more or have a BMI between 22 and 24.9 and exceed pre-pregnancy weight by at least 4.5 kg (10 lb) [73]. On average, by six weeks postpartum, women retain 3 to 6.8 kg of the weight gained during pregnancy, with Hispanic populations falling into the higher end of this range [6,8].…”
Section: Methodsmentioning
confidence: 99%
“…Maternal obesity increases health risks for mother and baby such as pre-eclampsia, gestational diabetes mellitus, hypertension disorders, delivery by caesarean section and stillbirth [2], [3]. These risks are present for women who are obese at the time they conceive but increase as women gain weight during pregnancy.…”
Section: Introductionmentioning
confidence: 99%